Implementación del proceso unificado de selección de inversiones – Óptima Capex - en una empresa distribuidora de energía eléctrica - Ortuzar Perez, Juan Carlos (2021)
This work of professional sufficiency consists in the implementation of a unique process for the selection of investment projects, in an electric power distribution company, subsidiary of its holding group. The electricity distribution companies, within their operating processes, have associated a large number of investment projects of various natures and circumstances, managed by the annual budgets approved in advance. To define these budgets, since different organizational areas and different companies are involved, different criteria are defined to assess the projects. These forms are not wrong, but they are different, which causes the allocation of economic resources does not always meet the fairest criteria. Given this scenario of different circumstances in which each investment project has been structured, looking for the object of choosing and making the best business decisions, it is necessary to use a methodology that can compare all the projects affected in the group, assess them with the same technical-economic criteria, and prioritize them in a specific order, in order to guarantee that the company will invest in the best projects. In other words, implement a unique investment selection process that is applied equally in each and every one of the group's companies, as a precondition to the allocation of annual economic budgets.